Studies in the selective synthesis of bidentate resorcinarene ligands - Kleinhans, Dewald Johannes (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2010.